Ai-powered Personalized Learning In Efl Acquisition: Exploring Adaptive Instruction And Feedback Systems - Dekhakhena, Abdelkrim (The Journal of Studies in Language, Culture, and Society, 2025)
The integration of Artificial Intelligence (AI) in English as a Foreign Language (EFL) instruction is revolutionizing traditional approaches by offering personalized learning experiences. This study investigates the potential of AI-powered adaptive learning systems to enhance EFL acquisition, focusing on how these technologies create individualized learning pathways and deliver real-time feedback. By examining AI-driven platforms that analyze student performance in areas such as grammar, pronunciation, and writing, this research evaluates their effectiveness in improving language fluency and retention compared to conventional teaching methods. Additionally, it addresses the pedagogical and ethical implications of AI in the classroom, including the balance between AI automation and the irreplaceable role of human educators. The study aims to provide a comprehensive understanding of how adaptive instruction, supported by AI, can transform EFL education and facilitate more tailored and efficient language acquisition.